Penerapan Data Mining Dengan Metode FP-Growth Untuk Menganalisis Pola Pembelian Konsumen - Ignasius Felix Salim; Mardiani Mardiani (Universitas Multi Data Palembang, 2026)
CV. Sukses Inti Prima is a distribution company engaged in the consumer goods sector, including both food and non-food products, operating in the South Sumatra region. In order to enhance the efficiency of sales strategies and inventory management, the company requires an analytical system capable of identifying customer purchasing patterns based on available transaction data. This study aims to implement data mining techniques using the FP-Growth algorithm to discover associations between products that are frequently purchased together. By leveraging the FP-Growth algorithm, the research is expected to successfully reveal purchasing patterns that can serve as a basis for developing marketing strategies, such as product bundling recommendations and more strategic product placement. These findings will also play a vital role in minimizing the risk of overstock or stockouts, while providing a data-driven foundation for business decision-making to increase product sales and customer satisfaction.